Laser-based 3D printing of pure NI powders - Moey, Sean Jon (2019)
Selective Laser Melting (SLM) is a metal 3D printing technology. It falls under powder bed fusion category according to ISO/ASTM. This technology allows the production of near full dense metal parts (>99% relative density) with complex shape and geometry in a relative short amount of time and other resources, as compared to traditional metal manufacturing methods. This report presents an experimental study on SLM of pure nickel with a step of 5 J/mm3 in volumetric energy density and the effects of printing parameters such as laser scanning speed, hatch spacing and powder layer thickness on the quality of printed parts. A total of 40 nickel samples and 4 sets of nickel tensile coupons were SLM fabricated. The relative build density, microstructure, microhardness of each samples were systematically studied, and tensile tests were performed. The highest relative build density of 99.44% was achieved using an energy density of 205.0 J/mm3 (a laser power of 200 W, a powder layer thickness of 25 μm, a hatch spacing of 25 μm and a laser scanning speed of 1560.8 mm/s). It was found that the powder layer thickness should be minimized (<50 μm) and the hatch spacing should be moderate (25 - 50μm) to achieve a favourable print quality. The highest microhardness was recorded at 168.8 HV for this sample. A tensile strength of 478.3 MPa, a yield strength of 367.6 MPa, a Young’s modulus of 216.03 GPa and ductility of 21.09% were achieved. Small and elongated grains as well as cellular sub-grain microstructures were observed in etched samples. This project paves the way for SLM printing of pure nickel components, which have applications as protective coatings and chemical catalysts. Further studies are recommended to determine the effects of other SLM parameters at a low powder layer thickness on SLM processing of pure nickel.